Minat Siswa/Siswi Sekolah Menengah Atas (SMA)/ Madrasah Aliyah (MA) Kota Kediri Melanjutkan Studi Di Perguruan Tinggi - Mukhammad Abdullah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2016)
Education is an important factor for the continuance of the country and a support factor which becomes an important role in entire sectors of life, because the life quality of a country is closely related to the level of education. To be able to become survive individuals in strict competition of working world, it is not enough for them having senior high school level of education; however, they need to have higher education. Therefore, in this study, it is important to know the interest of senior high school students (SMA/MA) in Kediri city to continue studying in higher education. The finding shows that, form 100% of expectation, the interest of SMA/MA students in Kediri city to continue studying in higher education is 15.542: 19.404 = 0.81 or 81%. Hence, it can be concluded that the interest of SMA/MA students to continue studying in higher education is big. The finding of this study can be basis information or reference to make a policy for STAIN Kediri to conduct efforts to build and repair the institution quality to improve the brand image or reputation of STAIN Kediri institution to be better so that it happens information dissemination orally to community, parents, and candidates of students that can improve the students’ interest to register in STAIN Kediri.